Simultaneous HPLC-DAD determination of pseudoephedrine HCl, sodium benzoate, sunset yellow, and methyl paraben in syrup preparation by use of partial least squares and principal component regression - Donmez, Ozlem Aksu; Dinc-Zor, Sule; Asci, Burge; Sen, Ecem (TAYLOR & FRANCIS INC, 2019)
The chromatographic methods (high performance liquid chromatography-diode array detection (HPLC-DAD)) combined with a partial least squares (type PLS-2) and principal component regression (PCR) were applied to the simultaneous determination of pseudoephedrine hydrochloride, sodium benzoate, sunset yellow, and methyl paraben in a syrup sample. By the aid of chromatographic data, the developed methods successfully solved the overlapped chromatographic peaks in HPLC analysis with the short elution time. A series of synthetic solutions containing different concentrations of analytes were used to check the prediction ability of the proposed methods. Satisfactory results were obtained by the PLS-2 and PCR methods for synthetic samples, with the average recoveries ranging from 98.33-100.20% to 98.44-100.07%, respectively. The developed methods were applied to a commercial syrup sample and the results were statistically compared with the conventional HPLC method. Considering the advantages of the chemometrics-assisted HPLC-DAD strategy, such as a short analysis time, simple and low-cost mobile phase, rapid sample preparation, the proposed methods could be an attractive alternative and green chromatography strategy for the determination of pseudoephedrine hydrochloride, sodium benzoate, sunset yellow, and methyl paraben in pharmaceutical samples.
Keywords: HPLC-DAD; multivariate calibration methods; preservative; pseudoephedrine hydrochloride; synthetic colorant; PERFORMANCE LIQUID-CHROMATOGRAPHY; INTERFERENCE-FREE DETERMINATION; CALIBRATION; QUANTITATION; RESOLUTION; DRUGS; 3-WAY; Biochemistry & Molecular Biology; Chemistry